The Effect of Giving Purple Sweet Potato Leaves Toward The Involution of Mother in The Posture and Sufficient Mother Breast Milk On Babies 0-6 Months - Malikha, Nur Zad; Prisusanti, Retno Dewi (Universitas STRADA Indonesia, 2019)
Background: One of the exclusive breastfeeding failures is because of low milk production, while uterine involution is also a complication that often occurs in the puerperium that can contribute to maternal mortality, nonpharmacological therapy that can be given, among others, the provision of purple sweet potato leaves.Purpose: The purpose of this study was to determine the effect of giving purple sweet potato leaves to uterine involution in puerperal mothers and the adequacy of breast milk.Method: This type of research is a quosy experimental only with a sample of 35, sampling with the Purposive Sampling technique. The provision of purple sweet potato leaves is given for 7 days, namely the 8-14 day of the puerperium, and measurement of uterine involution indicators and the adequacy of breast milk is done before and after administration of purple sweet potato leaves. Analysis using the Wilcoxon test.Results: The results of the study are the effect of giving purple sweet potato leaves to uterine involution in postpartum mothers and the adequacy of breast milk in infants 0-6 months (p-value = 0,000).Conclusion: There is an effect of giving purple sweet potato leaves to uterine involution in puerperal mothers and the adequacy of breast milk in infants aged 0-6 months